Syar’i Wedding Center Di Pekanbaru Dengan Pendekatan Arsitektur Islam - Achnia Tiffany Nurfadillah; Pedia Aldy; Gun Faisal (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Syar'i Wedding Center is a place to facilitate from the preparatory until the implementation of Islamic wedding that are in accordance with Islamic syari'at. In Pekanbaru, there is no building that has a special function for wedding processions and that applies the principle of syar'i in its services and facilities. Design application method of Islamic is in line with the functions of the building that will maximize concepts, themes, and design results both in form, appearance, ornamentation, zoning and material that will support the appearance of Islamic architectural styles. This design aims to facilitate the fulfillment of the needs of marriages in one area with the application of the principles of Islamic Architecture. Methods used include field data collection, literature study and empirical studies. The results of designed with the marriage bond concept which adopted the form and meaning of the application principles from Islamic Architecture in terms of varied forms of building that relate to the function, neutral building colors that resemble nature, using environmentally friendly and easily obtainable materials, different zoning applications, simple building, using ornaments and calligraphy that reminds God.Keywords: Islamic Architecture, Syar’i, The Marriage Bond, Wedding Center